2020
DOI: 10.3892/ol.2020.11922
|View full text |Cite
|
Sign up to set email alerts
|

<sup>18</sup>F‑FDG PET/CT SUV<sub>max</sub> and serum CEA levels as predictors for EGFR mutation state in Chinese patients with non‑small cell lung cancer

Abstract: The epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) contribute to an increased response rate, compared with chemotherapy, in patients with inhibitor-sensitive EGFR mutations. The present study evaluated the association between the maximum standardized uptake value (SUV max ) of 18 F-fluorodeoxyglucose positron emission tomography-computed tomography (FDG PET/CT), as well as serum carcinoembryonic antigen (CEA) levels and EGFR mutations prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…Some reports showed that there was no difference between EGFR-mutants and wild-type lung cancers regarding SUVmax. 11,12 In contrast, other evidences indicated that patients with lower [13][14][15][16][17][18][19] or higher [20][21][22] SUVmax were more likely to have EGFR mutations.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Some reports showed that there was no difference between EGFR-mutants and wild-type lung cancers regarding SUVmax. 11,12 In contrast, other evidences indicated that patients with lower [13][14][15][16][17][18][19] or higher [20][21][22] SUVmax were more likely to have EGFR mutations.…”
Section: Introductionmentioning
confidence: 91%
“…Several studies have reported that patients with low SUVmax, with cut-off values from ≤2.69 to <11.5, were more likely to have EGFR mutations than those with high SUVmax. [13][14][15][16][17][18][19] In contrary, some studies have reported that patients with higher SUVmax, with cutoffs from ≥6 to >13.65, were more likely to have EGFR mutations. [20][21][22] Our results are in favor that patients with higher SUVmax were more likely to have EGFR mutations.…”
Section: Dovepressmentioning
confidence: 97%
See 3 more Smart Citations